Intoxicação medicamentosa: relacionada ao uso indiscriminado de medicamentos - Gonçalves, Claudiana Aguilar; Gonçalves, Cleide Avilar; Dos Santos, Valdeir Areia dos Santos Areia; Sarturi, Leandro; Terra Júnior, André Tomaz (Revista Científica da Faculdade de Educação e Meio Ambiente, 2017)
As intoxicações medicamentosas esta se tornando um problema alarmante de saúde publica segundo publicado pelo Sistema Nacional de Informações Tóxico-Farmacológicas (SINITOX) Os medicamentos ocupam o primeiro lugar nas intoxicações no Brasil. O propósito do presente artigo tem como objetivo realizar uma revisão bibliográfica dos casos de intoxicações medicamentosas envolvendo todas faixas etárias e as causas determinantes. Fazendo necessária destacar o papel do Profissional farmacêutico, para dispensarão orientação alem de prestar Assistência farmacêutica quanto ao uso racional de medicamentos em todos os aspectos da farmacoterapia. ABSTRACT: Drug intoxications are becoming an alarming public health problem as published by the National Toxic-Pharmacological Information System (SINITOX). Medicines are the number one poisoning in Brazil. The purpose of this article is to carry out a bibliographical review of the cases of drug intoxications involving all age groups and the determining causes. Making it necessary to highlight the role of the pharmaceutical professional, for dispensing guidance as well as providing pharmaceutical assistance regarding the rational use of drugs in all aspects of pharmacotherapy. This study is a review of the literature covering drug intoxications, indiscriminate drug use and self-medication. The main causes of this problem are the abusive use of the drug due to lack of knowledge about its dosage and administration, prescription errors and self-medication.